2023
DOI: 10.1002/bit.28461
|View full text |Cite
|
Sign up to set email alerts
|

Scaling eukaryotic cell‐free protein synthesis achieved with the versatile and high‐yielding tobacco BY‐2 cell lysate

Abstract: Eukaryotic cell‐free protein synthesis (CFPS) can accelerate expression and high‐throughput analysis of complex proteins with functionally relevant post‐translational modifications (PTMs). However, low yields and difficulties scaling such systems have prevented their widespread adoption in protein research and manufacturing.Here, we provide detailed demonstrations for the capabilities of a CFPS system derived from Nicotiana tabacum BY‐2 cell culture (BY‐2 lysate; BYL). BYL is able to express diverse, functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Our chloroplast-based system is unique from the previously published tobacco BY-2 cell lysate system, , which is a highly productive expression system capable of combined transcription, translation, and protein modification. Specifically, the BY-2 lysate system is a eukaryotic chromosomal system and thus is different.…”
Section: Discussionmentioning
confidence: 99%
“…Our chloroplast-based system is unique from the previously published tobacco BY-2 cell lysate system, , which is a highly productive expression system capable of combined transcription, translation, and protein modification. Specifically, the BY-2 lysate system is a eukaryotic chromosomal system and thus is different.…”
Section: Discussionmentioning
confidence: 99%
“…Although E.coli cell-free protein synthesis is widely used, the prokaryotic cell lysate offers limited post-translational modifications and thus fewer issues in the production of complex proteins [19]. On the other hand, post-translational modifications and optimal folding conditions are possible in eukaryotic cell-free protein production systems based on mammalian, insect, and tobacco cells [20][21][22]. Moreover, it was shown that membrane proteins can be translocated into vesicles derived from the endoplasmic reticulum (ER), termed microsomes, to facilitate the production of active ion channels in CHO and insect cell-free systems [23].…”
Section: Plasmidsmentioning
confidence: 99%
“…Eukaryotic lysates can include machinery capable of PTMs and yields have been increased thanks to the adoption of T7-polymerase systems to allow coupled transcription-translation within the same system [6]. Notably, a CFPE system based on Nicotiana tabacum BY-2 lysate is capable of PTM incorporation, high specific yields, and can be effectively scaled between the microlitre and litre ranges [7,8]. Such systems allow the expression of eYFP at up to 3 mg/ml lysate used over a 48-hour synthesis [8].…”
Section: Introductionmentioning
confidence: 99%